Does dietary creatine supplementation have a role to play in exercise metabolism? - Greenhaff, P. L. (1996)
- The Biosynthesis and Distribution of Creatine - The Role of Creatine in Muscle Energy Metabolism and Fatigue - The Effect of Creatine Ingestion on Muscle Creatine Concentration in Humans - The Effect of Creatine Ingestion on Exercise Performance - Creatine's Mechanism of Action - Future Work